The new Damascus document: the midrash on the eschatological Torah of the Dead Sea Scrolls : reconstruction, translation and commentary - Wacholder, Ben Zion (Studies on the texts of the desert of Judah, 2007)
Preliminary Material /B.Z. Wacholder -- Chapter One. Introduction /B.Z. Wacholder -- Chapter Two. Text And Translation /B.Z. Wacholder -- Chapter Three. Commentary /B.Z. Wacholder -- Chapter Four. Unincorporated Fragments /B.Z. Wacholder -- Bibliography /B.Z. Wacholder -- Index Of Modern Authors /B.Z. Wacholder -- Subject Index /B.Z. Wacholder -- Index Of Ancient Sources /B.Z. Wacholder.